خصوصية الجرائم الواقعة على أمن الدولة في مجال الصياغة التشريعية والمصلحة المحمية - ساهر, إبراهيم الوليد; نصـار, عدلي عبد الفتاح (Revue jurisprudence, 2018)
هدفت هذه الدراسة إلى كيفية معالجة المشرع العقابي الفلسطيني للجرائم الواقعة على أمن الدولة في مجال الصياغة التشريعية للنصوص العقابية ذات العلاقة، إضافة إلى كيفية معالجته للمصلحة التي يستهدف المشرع حمايتها؛ نظراً للخصوصية التي تتمتع بها هذه الطائفة من الجرائم، وذلك بتبيان الليونة والمرونة التي أضفاها المشرع على القوالب التشريعية من ناحية، وعلى التوسع الذي خصّه للمصلحة المحمية بمجرد تعريضها للخطر من ناحية أخرى. وقد اتبعت هذه الدراسة المنهج التحليلي لنصوص القوانين العقابية ذات العلاقة النافذة في فلسطين، إضافة إلى المنهج المقارن الذي هَيَّأ لها الوقوف على نقاط الالتقاء ومواطن الافتراق بين تلك القوانين، وما اشتملت عليه من محاسن وما شابها من قصور أو مثالب، إظهاراً لما هو كائن، سعياً لما ينبغي أن يكون الحال والمآل.            وخلصت هذه الدراسة إلى نتائج كان أهمها، انجراف المشرع الفلسطيني مع تيار التوسع والمرونة في صياغته للقوالب التشريعية وفي سياسته التحوطية لهذه الطائفة من الجرائم، الأمر الذي أخلّ بالتوازن الحقيقي بين المصلحة المحمية وبين المبادئ الدستورية التي تتعلق بالتجريم والعقاب.            الكلمات المفتاحية: جرائم، أمن الدولة، خصوصية، القوالب التشريعية، السياسة التحوّطية. Abstract: This study sheds light on crimes against the state security regarding the legislative phrasing in the relevant penal provisions. In addition, it seeks to reveal the ways that are followed in protecting the interest affected by those crimes due to their sui generis nature. The researcher aims to highlight the flexibility that the legislator gave to the legislative structures on the one hand and to the expansion of the protected interest once it is at risk on the other hand. This study is an analytical one, where it the analyzes the relevant penal laws that are enforced in Palestine. Moreover, the study adopts the comparative approach since it enables the researcher to identify the points of similarity and difference among those laws, and the advantages or the drawbacks; in order to present their actuality; seeking to achieve their prospective form. The study reached sum of outcomes. The most important among those outcomes is that of deviation of the Palestinian legislator towards the trend of expansion and flexibility in the formulation of legislative structures and in its precautionary policy regarding such crimes, which undermines the real balance between the protected interest and the constitutional principles of incrimination and penalization. Keywords : Crimes, The Security of the State, Distinction, Legislative- structures, Precautionary policy.